Penarikan Zakat Nasabah Di Bank Bjb Syariah Kabupaten Garut (Jl. Ciledug No 45 Kabupaten Garut) (Studi Kasus Di Bank BJB Syariah Kabupaten Garut) - Wati, Ai; Radiansyah, Elshandy (STAI Al Musaddadiyah Garut, 2022)
BJB Syariah Garut Regency JL. Ciledug No 45 is a Sharia financial institution. One of its functions is to collect funds from customers to be managed. Its product, Savings, involves the opening of savings accounts for customers. These savings utilize the Al-mudharabah contract, which entails rights and obligations for each party. The research problem addressed in this study includes 1) Analysis of customer zakat withdrawals at Bank BJB Syariah in Garut Regency according to Islamic economic law, 2) How zakat withdrawal mechanisms and laws are applied in Bank BJB Syariah Garut Regency from the perspective of Islamic law. The research aims to: 1) Analyze customer zakat withdrawals at Bank BJB Syariah in Garut Regency according to Islamic Law, 2) Understand the mechanisms and laws of zakat withdrawal at Bank BJB Syariah Garut Regency from the perspective of Islamic law. The research method used is descriptive, involving studying, analyzing, and presenting data related to the issue. Data collection methods include data analysis, observation, interviews, and literature review. The data type is qualitative, describing the process of customer zakat withdrawals by Bank BJB Syariah. The research findings on zakat withdrawals in savings products at Bank BJB Syariah Garut Regency state that customers agree to a 2.5% zakat deduction each month upon opening their account. This deduction is implemented regardless of the nisab and haul. If customers agree, regardless of profit sharing or the amount of savings, 2.5% zakat is deducted monthly and directed to BAZNAS or ACT. Zakat withdrawals in Bank BJB Syariah savings embody the principle of social solidarity. The bank must consider nisab and haul in zakat withdrawals to comply with Islamic law. Keywords: Islamic Law, Customer, Zakat.